Non-Barrett’s esophageal and gastric tumors: diagnosis and treatment - Ciocirlan, M.; Gincul, R.; Lepilliez, V.; Pioche, M.; Ionescu, M. E.; Diculescu, M. M. (Endoscopy, 2012)
The 2012 Digestive Disease Week (DDW; 19 – 22 May, San Diego, California, USA) presented small-step advances in the field of non-Barrett’s esophageal and gastric tumors. In patients with ear – nose – throat (ENT) cancer, narrow-band imaging (NBI) might be useful in endoscopic screening for early esophageal squamous neoplasia, but confirmation of its role has yet to be reported. The yield and intervals of endoscopic screening for gastric neoplasia are better understood, and so are the results and complications of gastroesophageal endoscopic submucosal dissection (ESD) together with their predictive factors. Endoscopic therapy of advanced tumors was another important theme at DDW, with ESD after radiotherapy for advanced esophageal cancer and gastrojejunostomy for neoplastic gastric outlet obstruction being reported. Relevant abstracts are discussed below.